2018
DOI: 10.1159/000495217
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Urinary Extracellular Vesicle Fibroblast-Specific Protein 1 in Patients with Active Crescentic Glomerulonephritis

Abstract: Background/Aims: Extracellular vesicles (EVs), including exosomes, are present in various bodily fluids, including urine. We and others previously reported that cells expressing fibroblast-specific protein 1 (FSP1) accumulate within damaged glomeruli, and that urinary FSP1, as well as urinary soluble CD163, could potentially serve as a biomarker of ongoing glomerular injury. Methods: To test that idea, we collected urine samples from 37 patients with glomerular disease; purified the urinary EVs; characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…EV‐based biomarkers in urine are currently investigated for an array of malignancies and other diseases such as polycystic kidney disease (Raimondo et al., 2016; Salih et al., 2016), cystinuria (Bourderioux et al., 2015), diabetes (Abe et al., 2018; Lytvyn et al., 2017; Zubiri et al., 2014), renal ischemia‐reperfusion injury (Sonoda et al., 2009), glomerulonephritis (Morikawa et al., 2018), renal interstitial fibrosis (Carreras‐Planella et al., 2020; Chun‐Yan et al., 2018), hypertension or lupus nephritis (Tangtanatakul et al., 2018) and in calcineurin inhibitor‐induced nephrotoxicity (Carreras‐Planella et al., 2020). However, many of the identified candidate biomarkers have not yet been validated in large independent cohorts or tested in more than one laboratory.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…EV‐based biomarkers in urine are currently investigated for an array of malignancies and other diseases such as polycystic kidney disease (Raimondo et al., 2016; Salih et al., 2016), cystinuria (Bourderioux et al., 2015), diabetes (Abe et al., 2018; Lytvyn et al., 2017; Zubiri et al., 2014), renal ischemia‐reperfusion injury (Sonoda et al., 2009), glomerulonephritis (Morikawa et al., 2018), renal interstitial fibrosis (Carreras‐Planella et al., 2020; Chun‐Yan et al., 2018), hypertension or lupus nephritis (Tangtanatakul et al., 2018) and in calcineurin inhibitor‐induced nephrotoxicity (Carreras‐Planella et al., 2020). However, many of the identified candidate biomarkers have not yet been validated in large independent cohorts or tested in more than one laboratory.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…These results were the foundation for a prostate cancer diagnostic test that has been extensively validated in two prospective multi‐center US studies (McKiernan et al., 2016; McKiernan et al., 2018). Altogether, these promising results inspired the search for uEV‐based biomarkers for other urogenital tract pathologies such as polycystic kidney disease, cystinuria, diabetic nephropathy, acute kidney injury/ renal ischemia‐reperfusion injury, glomerulonephritis, renal interstitial fibrosis/ chronic kidney disease, lupus nephritis, nephronophthisis‐related ciliopathies, tubulopathies and primary and secondary hypertension (Abe et al., 2018; Bourderioux et al., 2015; Chun‐Yan et al., 2018; Corbetta et al., 2015; Gonzalez‐Calero et al., 2017; Kwon et al., 2017; La Salvia et al., 2020; Morikawa et al., 2018; Qi et al., 2016; Raimondo et al., 2016; Raimondo et al., 2020; Salih et al., 2016; Salih et al., 2018; Sonoda et al., 2009; Stokman et al., 2019; Tangtanatakul et al., 2018; van der Lubbe et al., 2012; Williams et al., 2020; Wolley et al., 2017; Zubiri et al., 2014). Many of the newly identified candidate biomarkers have not yet been validated in large independent cohorts or in additional laboratories, but nevertheless these examples highlight the enormous potential for uEV analyses as readouts for pathophysiological alterations within the urogenital and other systems.…”
Section: Introductionmentioning
confidence: 99%
“…Crescent formation, the hallmark of RPGN, has been associated with the presence of fibroblast-specific protein 1 (FSP1), a cytosolic protein expressed by increased number of renal cells in kidneys exhibiting ongoing injury [ 69 ]. In idiopathic membranous nephropathy, upregulation of blood and urinary MUC3A circular RNA (circRNA) and various small nucleolar RNAs (snoRNAs) such as SNORA51, SNORA31, SNORA70, SNORA75, and SNORD112 has been reported [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, level of fibroblast-specific protein 1 (FSP1) has been shown to increase in extracellular vesicles (including exosomes) derived from patients with active crescentic glomerulonephritis (Morikawa et al, 2019). Interestingly, its level was decreased after immunosuppressive therapy (Morikawa et al, 2019).…”
Section: Lupus Nephritis and Other Glomerular Diseasesmentioning
confidence: 97%
“…For other glomerular diseases, a previous study using a proteomics approach has shown that urinary exosomal aminopeptidase N, vasorin precursor, a-1-antitrypsin, and ceruloplasmin could differentiate immunoglobulin A (IgA) nephropathy from thin basement membrane nephropathy and healthy controls (Moon et al, 2011). In another study, level of fibroblast-specific protein 1 (FSP1) has been shown to increase in extracellular vesicles (including exosomes) derived from patients with active crescentic glomerulonephritis (Morikawa et al, 2019). Interestingly, its level was decreased after immunosuppressive therapy (Morikawa et al, 2019).…”
Section: Lupus Nephritis and Other Glomerular Diseasesmentioning
confidence: 98%